Curable resin composition, fiber-reinforced molding material and molded article using the same
The curable resin composition, featuring a brominated vinyl ester, 1,3-butanediol dimethacrylate, polyisocyanate, and polymerization initiator, enhances impregnability, flowability, and flame retardancy in fiber-reinforced molding materials, overcoming the challenges faced by existing technologies.
Patent Information
- Application Number
- JP2023155540
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
Fiber-reinforced molding materials face challenges in achieving excellent impregnability and molding flowability while also meeting flame retardancy standards, as reducing unsaturated monomer content can impair impregnation and flowability, and increasing it can lead to excessive fluidity and burrs.
A curable resin composition containing a brominated vinyl ester, an unsaturated monomer such as 1,3-butanediol dimethacrylate, a polyisocyanate, and a polymerization initiator, with specific molar ratios and concentrations to optimize impregnability, flowability, and flame retardancy.
The composition achieves a fiber-reinforced molding material with excellent impregnability and molding flowability, along with a molded product that exhibits superior flame retardancy, thereby addressing the limitations of existing technologies.
Smart Images

Figure 2025047196000001 
Figure 2025047196000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition, a fiber-reinforced molding material, and a molded article using the same. [Background technology]
[0002] Conventionally, fiber-reinforced molding materials are known that are obtained by impregnating a thermosetting resin composition such as vinyl ester or unsaturated polyester resin with reinforcing fibers such as carbon fibers (for example, Patent Document 1). As a molding method using the fiber-reinforced molding material, a method is known in which intermediate materials called sheet molding compound (SMC) or bulk molding compound (BMC) are used and cured and molded by a method such as press molding or injection molding.
[0003] The fiber-reinforced molding material has attracted attention for its characteristics of being lightweight yet excellent in heat resistance and mechanical strength, and is being used in a wide range of applications such as housings for automobiles and aircraft. Molded products using the fiber-reinforced molding material are required to meet certain flame retardancy standards depending on the application.
[0004] In order to improve the flame retardancy of a molded product using the fiber-reinforced molding material, it is possible to reduce the organic components in the thermosetting resin composition, for example, to reduce the content of the unsaturated monomer in the thermosetting resin composition. However, when the content of the unsaturated monomer is reduced, there is a disadvantage that the impregnation of the thermosetting resin composition into the carbon fiber may decrease, or the molding flowability of the fiber-reinforced molding material may decrease. In addition, when the content of the unsaturated monomer is increased, there is a disadvantage that the molding flowability may become too large, resulting in the generation of burrs. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6241583 Summary of the Invention [Problem to be solved by the invention]
[0006] The problem to be solved by the present invention is to provide a fiber-reinforced molding material having excellent impregnation properties and molding flowability, and a curable resin composition capable of realizing a molded article having excellent flame retardancy, a fiber-reinforced molding material, and a molded article using the same. [Means for solving the problem]
[0007] The present inventors have found that by using a specific vinyl ester in a curable resin composition and setting the content of an unsaturated monomer within a specific range, a fiber-reinforced molding material having excellent impregnation properties and molding flowability, and a molded product having excellent flame retardancy, can be obtained, and have completed the present invention.
[0008] That is, the curable resin composition of the present invention contains a brominated vinyl ester (A), an unsaturated monomer (B), a polyisocyanate (C), and a polymerization initiator (D), wherein the unsaturated monomer (B) is a methacrylate containing 1,3-butanediol dimethacrylate, and the unsaturated monomer (B) is contained in an amount in the range of 25 parts by mass or more and 40 parts by mass or less relative to 80 parts by mass of the brominated vinyl ester (A). Effect of the Invention
[0009] The curable resin composition of the present invention can provide a fiber-reinforced molding material having excellent impregnation properties and molding flowability, and can also provide a molded product having excellent flame retardancy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The curable resin composition of the present invention contains a brominated vinyl ester (A), an unsaturated monomer (B), a polyisocyanate (C), and a polymerization initiator (D), and contains 1,3-butanediol dimethacrylate as the unsaturated monomer (B). The unsaturated monomer (B) is contained in a range of 25 parts by mass or more and 40 parts by mass or less per 80 parts by mass of the brominated vinyl ester (A), and the molar ratio (NCO / OH ratio) of an isocyanate group (NCO) of the polyisocyanate (C) to a hydroxyl group (OH) of the brominated vinyl ester (A) is in a range of 0.40 or more and 0.70 or less.
[0011] The brominated vinyl ester (A) can be obtained, for example, by reacting a brominated epoxy resin (a1) having an epoxy equivalent in the range of 180 to 500 with (meth)acrylic acid (a2). In this specification, "(meth)acrylic acid" refers to either or both of acrylic acid and methacrylic acid.
[0012] Examples of the epoxy resin (a1) include bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol fluorene type epoxy resins, and biscresol fluorene type epoxy resins, novolac type epoxy resins such as phenol novolac type epoxy resins and cresol novolac type epoxy resins, oxopropylidone modified epoxy resins, and brominated epoxy resins of these resins; glycidyl ethers of phenols such as dipropylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl ethers of alkylene oxide adducts of bisphenol A, and glycidyl ethers of polyhydric alcohols such as diglycidyl ether of hydrogenated bisphenol A. Examples of epoxy resins include alicyclic epoxy resins such as 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate and 1-epoxyethyl-3,4-epoxycyclohexane, glycidyl esters such as phthalic acid diglycidyl ester, tetrahydrophthalic acid diglycidyl ester, diglycidyl-p-oxybenzoic acid and dimer acid glycidyl ester, glycidyl amines such as tetraglycidyldiaminodiphenylmethane, tetraglycidyl-m-xylenediamine, triglycidyl-p-aminophenol and N,N-diglycidylaniline, and heterocyclic epoxy resins such as 1,3-diglycidyl-5,5-dimethylhydantoin and triglycidyl isocyanurate. Among these, bifunctional aromatic epoxy resins are preferred because they are superior in strength of molded products, handling of molding materials, and flowability of molding materials during molding, and bisphenol A type epoxy resins and bisphenol F type epoxy resins are more preferred. These epoxy resins can be used alone or in combination of two or more kinds. When two or more kinds of epoxy resins are used in combination, the epoxy equivalent of the epoxy resin (a1) is the average epoxy equivalent of all the epoxy resins.
[0013] The brominated epoxy resin (a1) may be used after being polymerized with a dibasic acid such as bisphenol A in order to adjust the epoxy equivalent.
[0014] The reaction between the brominated epoxy resin (a1) and the (meth)acrylic acid (a2) is preferably carried out using an esterification catalyst at a temperature of 60 to 140° C. A polymerization inhibitor or the like may also be used.
[0015] The curable resin composition of the present invention essentially contains 1,3-butanediol dimethacrylate as the unsaturated monomer (B), and contains the unsaturated monomer (B) in an amount of 25 parts by mass or more and 40 parts by mass or less per 80 parts by mass of the brominated vinyl ester (A).
[0016] The curable resin composition of the present invention can obtain a fiber-reinforced molding material having excellent impregnation and molding flowability, and can obtain a molded product having excellent flame retardancy, by making the content of the unsaturated monomer (B) within the above range. When the content of the unsaturated monomer (B) is less than 25 parts by mass relative to 80 parts by mass of the brominated vinyl ester (A), the fiber-reinforced molding material cannot ensure sufficient impregnation into the reinforcing fiber (E) described below, or the fiber-reinforced molding material cannot ensure sufficient molding flowability. On the other hand, when the content of the unsaturated monomer (B) is more than 40 parts by mass relative to 80 parts by mass of the brominated vinyl ester (A), the molding flowability of the fiber-reinforced molding material becomes too large, causing flashing, or a molded product having excellent flame retardancy cannot be obtained.
[0017] In order to achieve both flame retardancy and impregnation properties, the curable resin composition of the present invention preferably contains 20 to 40 parts by mass of 1,3-butanediol dimethacrylate per 80 parts by mass of the brominated vinyl ester (A).
[0018] The curable resin composition of the present invention may contain, as the unsaturated monomer (B), other methacrylates in addition to 1,3-butanediol dimethacrylate. Other methacrylates include, for example, monofunctional methacrylate compounds such as benzyl methacrylate, phenoxyethyl methacrylate, phenoxy polyethylene glycol methacrylate, polyethylene glycol methacrylate alkyl ether, polypropylene glycol methacrylate alkyl ether, 2-ethylhexyl methacrylate, isodecyl methacrylate, lauryl methacrylate, isotridecyl methacrylate, n-stearyl methacrylate, tetrahydrofurfuryl methacrylate, isobornyl methacrylate, dicyclopentenyloxyethyl methacrylate, and dicyclopentanyl methacrylate; dimethacrylate compounds such as ethylene glycol dimethacrylate, propylene glycol dimethacrylate, 1,4-butanediol dimethacrylate, 1,3-butanediol dimethacrylate, neopentyl glycol dimethacrylate, 1,6-hexanediol dimethacrylate, bisphenol dimethacrylate, and 1,4-cyclohexanedimethanol dimethacrylate; and diallyl phthalate and divinylbenzene. Among these, methacrylates having aromatic groups are preferred, and benzyl methacrylate and phenoxyethyl methacrylate are more preferred, since they provide a molding material with higher strength. The other methacrylates may be used alone or in combination of two or more. In addition to 1,3-butanediol dimethacrylate, the unsaturated monomer (B) may contain an acrylate.
[0019] Examples of the polyisocyanate (C) include diphenylmethane diisocyanate (4,4'-, 2,4'-, or 2,2'-isomer, or a mixture thereof), diphenylmethane diisocyanate modified products such as carbodiimide modified products, nurate modified products, biuret modified products, and urethane imine modified products of diphenylmethane diisocyanate, polyol modified products modified with a polyol having a number average molecular weight of 1,000 or less, such as diethylene glycol or dipropylene glycol, tolylene diisocyanate, tolidine diisocyanate, polymethylene polyphenylene polyisocyanate, and the like. Aromatic polyisocyanates such as naphthalene diisocyanate, xylylene diisocyanate, 1,5-naphthalene diisocyanate, and tetramethylxylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, and norbornene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate, nurate modified product of hexamethylene diisocyanate, biuret modified product, adduct, and dimer acid diisocyanate can be used. Among these, aromatic polyisocyanates are preferred, and carbodiimide modified products of diphenylmethane diisocyanate are more preferred, since molding materials excellent in handling (film peelability and tackiness) can be obtained. Carbodiimide modified products of diphenylmethane diisocyanate include those having a carbodiimide group, as well as those having a urethane imine structure in which an isocyanate group is further added to the carbodiimide group. Moreover, these polyisocyanates (C) may be used alone or in combination of two or more kinds.
[0020] In the curable resin composition of the present invention, the molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) is 0.4 to 0.7. If the molar ratio is less than 0.4, the handling properties such as film peelability and tackiness are reduced, while if the molar ratio exceeds 0.7, the molding flowability is reduced.
[0021] The polymerization initiator (D) is not particularly limited, but is preferably an organic peroxide. For example, diacyl peroxide compounds, peroxy ester compounds, hydroperoxide compounds, ketone peroxide compounds, alkyl perester compounds, percarbonate compounds, peroxy ketals, etc. can be mentioned, and can be appropriately selected according to molding conditions. These polymerization initiators (D) may be used alone or in combination of two or more kinds.
[0022] Among these, it is preferable to use a polymerization initiator having a temperature of 70°C or more and 110°C or less to obtain a 10-hour half-life in order to shorten the molding time. If the temperature is 70°C or more and 110°C or less, the life of the fiber-reinforced molding material at room temperature is long, and it is preferable because it can be cured in a short time by heating, and the balance between curability and moldability is better. Examples of such polymerization initiators include 1,6-bis(t-butylperoxycarbonyloxy)hexane, 1,1-bis(t-butylperoxy)cyclohexane, 1,1-bis(t-amylperoxy)cyclohexane, 1,1-bis(t-hexylperoxy)cyclohexane, t-butylperoxydiethyl acetate, t-butylperoxyisopropyl carbonate, t-amylperoxyisopropyl carbonate, t-hexylperoxyisopropyl carbonate, di-tert-butylperoxyhexahydroterephthalate, and t-amylperoxytrimethylhexanoate.
[0023] The content of the polymerization initiator (D) is preferably within a range of 0.3 to 3 mass % based on the total amount of the brominated vinyl ester (A) and the unsaturated monomer (B) because both the curing characteristics and storage stability are excellent.
[0024] The curable resin composition of the present invention essentially comprises the brominated vinyl ester (A), the unsaturated monomer (B), the polyisocyanate (C), and the polymerization initiator (D), but may contain other components, such as thermosetting resins other than the brominated vinyl ester (A), thermoplastic resins, polymerization inhibitors, curing accelerators, fillers, shrinkage reducing agents, mold release agents, thickeners, viscosity reducers, pigments, antioxidants, plasticizers, flame retardants, antibacterial agents, ultraviolet stabilizers, reinforcing materials, and photocuring agents.
[0025] Examples of the thermosetting resin include vinyl urethane resin, unsaturated polyester resin, acrylic resin, epoxy resin, phenol resin, melamine resin, furan resin, etc. These thermosetting resins may be used alone or in combination of two or more kinds.
[0026] Examples of the thermoplastic resin include polyamide resin, polyethylene terephthalate resin, polybutylene terephthalate resin, polycarbonate resin, urethane resin, polypropylene resin, polyethylene resin, polystyrene resin, acrylic resin, polybutadiene resin, polyisoprene resin, and resins modified by copolymerization, etc. These thermoplastic resins may be used alone or in combination of two or more kinds.
[0027] Examples of the polymerization inhibitor include hydroquinone, trimethylhydroquinone, pt-butylcatechol, t-butylhydroquinone, toluhydroquinone, p-benzoquinone, naphthoquinone, hydroquinone monomethyl ether, phenothiazine, copper naphthenate, copper chloride, 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl, etc. These polymerization inhibitors may be used alone or in combination of two or more kinds.
[0028] Examples of the curing accelerator include metal soaps such as cobalt naphthenate, cobalt octenate, vanadyl octenate, copper naphthenate, and barium naphthenate, and metal chelate compounds such as vanadyl acetylacetate, cobalt acetylacetate, and iron acetylacetonate. Examples of amines include N,N-dimethylamino-p-benzaldehyde, N,N-dimethylaniline, N,N-diethylaniline, N,N-dimethyl-p-toluidine, N-ethyl-m-toluidine, triethanolamine, m-toluidine, diethylenetriamine, pyridine, phenylmorpholine, piperidine, and diethanolaniline. These curing accelerators may be used alone or in combination of two or more.
[0029] The fillers include inorganic compounds and organic compounds, and can be used to adjust the physical properties of the molded product, such as strength, elastic modulus, impact strength, and fatigue durability.
[0030] Examples of the inorganic compound include calcium carbonate, magnesium carbonate, barium sulfate, mica, talc, kaolin, clay, celite, asbestos, barite, baryta, silica, silica sand, dolomite limestone, gypsum, aluminum fine powder, hollow balloons, alumina, glass powder, aluminum hydroxide, kansuiite, zirconium oxide, antimony trioxide, titanium oxide, molybdenum dioxide, and iron powder.
[0031] The organic compounds include natural polysaccharide powders such as cellulose and chitin, and synthetic resin powders. As the synthetic resin powders, organic powders composed of hard resins, soft rubbers, elastomers, polymers (copolymers), and particles having a multilayer structure such as a core-shell type can be used. Specific examples include particles composed of butadiene rubber and / or acrylic rubber, urethane rubber, silicone rubber, polyimide resin powder, fluororesin powder, and phenol resin powder. These fillers may be used alone or in combination of two or more.
[0032] Examples of the release agent include zinc stearate, calcium stearate, paraffin wax, polyethylene wax, carnauba wax, etc. Preferred are paraffin wax, polyethylene wax, carnauba wax, etc. These release agents may be used alone or in combination of two or more.
[0033] Examples of the thickener include metal oxides and hydroxides such as magnesium oxide, magnesium hydroxide, calcium oxide, and calcium hydroxide, and acrylic resin-based fine particles, which can be appropriately selected depending on the handleability of the fiber-reinforced molding material of the present invention. These thickeners may be used alone or in combination of two or more kinds.
[0034] The curable resin composition of the present invention contains at least bromine derived from the brominated vinyl ester (A). The curable resin composition can obtain flame retardancy by containing bromine. In order to further improve the flame retardancy, the bromine concentration in the curable resin composition is preferably 20% by mass or more, more preferably 23% by mass or more.
[0035] The bromine concentration can be calculated by the following method. The mass of bromine contained in the brominated vinyl ester (A) is a value calculated from the chemical formula and mass of the brominated vinyl ester (A). The total mass of the curable resin composition is the mass excluding the carbon fiber (E) described later, if any. Bromine concentration [mass%] = (mass of bromine contained in brominated vinyl ester (A)) / (total mass of curable resin composition) × 100
[0036] The curable resin composition of the present invention preferably has a viscosity measured at a temperature of 25° C. of 1000 mPa·s or more and 12000 mPa·s or less, since this further improves the impregnation into the reinforcing fibers (E).
[0037] The fiber-reinforced molding material of the present invention is characterized by containing the above-mentioned curable resin composition and reinforcing fibers (E).
[0038] Examples of the reinforcing fiber (E) include carbon fiber, glass fiber, silicon carbide fiber, alumina fiber, boron fiber, metal fiber, aramid fiber, vinylon fiber, tetron fiber, and other organic fibers. Carbon fiber or glass fiber is preferred, and carbon fiber is more preferred, because it provides a molded product with higher strength and elasticity. These reinforcing fibers (E) may be used alone or in combination of two or more.
[0039] When carbon fibers are used as the reinforcing fibers (E), various types of fibers can be used, such as polyacrylonitrile-based, pitch-based, rayon-based, etc. Among these, polyacrylonitrile-based fibers are preferred because they can easily produce high-strength carbon fibers.
[0040] The number of filaments in the fiber bundle used as the carbon fiber is preferably 1,000 to 60,000, as this further improves the resin impregnation property and the mechanical properties of the molded product.
[0041] The carbon fibers are preferably cut to a length of 2.5 to 50 mm, and more preferably cut to a length of 5 to 40 mm, because this improves the flowability in the mold during molding, and the appearance and mechanical properties of the molded product.
[0042] The fiber-reinforced molding material of the present invention preferably contains the reinforcing fiber (E) in the range of 20% by mass to 70% by mass, since the mechanical properties of the resulting molded article are further improved. If the content of the reinforcing fiber is less than 20% by mass, the strength of the molded article may be insufficient, and if it exceeds 70% by mass, the impregnation of the curable resin composition into the reinforcing fiber (E) may be insufficient, causing the molded article to blister, resulting in insufficient strength of the molded article.
[0043] Furthermore, when the fiber-reinforced molding material of the present invention contains cut carbon fibers as the reinforcing fibers (E), it is preferable that the carbon fibers are impregnated into the curable resin composition with their fiber directions random.
[0044] From the viewpoints of excellent productivity and moldability with design diversity, the fiber-reinforced molding material of the present invention is preferably a sheet molding compound (SMC) or a bulk molding compound (BMC).
[0045] The method for producing the SMC includes mixing and dispersing each component such as the brominated vinyl ester (A), the unsaturated monomer (B), the polyisocyanate (C), and the polymerization initiator (D) using a mixer such as a normal mixer, intermixer, planetary mixer, roll, kneader, or extruder, applying the obtained curable resin composition to a uniform thickness on carrier films placed above and below, sandwiching the reinforcing fiber (E) between the curable resin composition on the carrier films placed above and below, and then passing the whole between impregnation rolls to impregnate the reinforcing fiber (E) with the curable resin composition by applying pressure, and then winding it up into a roll or folding it in a zigzag shape. Furthermore, it is preferable to perform aging at a temperature of 25 to 60°C after this. As the carrier film, a polyethylene film, a polypropylene film, a laminate film of polyethylene and polypropylene, polyethylene terephthalate, nylon, etc. can be used.
[0046] The method for producing the BMC may be, as in the method for producing the SMC, a method in which the brominated vinyl ester (A), the unsaturated monomer (B), the polyisocyanate (C), the polymerization initiator (D), and other components are mixed and dispersed using a mixer such as a normal mixer, intermixer, planetary mixer, roll, kneader, extruder, etc., and the reinforcing fiber (E) is mixed and dispersed in the obtained curable resin composition. Also, as in the case of the SMC, it is preferable to age the composition at a temperature of 25 to 60°C.
[0047] From the viewpoints of excellent productivity and excellent design diversity obtained from the fiber-reinforced molding material, the molding method of the molded article of the present invention is preferably hot compression molding of SMC or BMC.
[0048] The heat compression molding is, for example, a manufacturing method in which a molding material such as SMC or BMC is weighed out in a predetermined amount, put into a mold preheated to 110 to 180°C, clamped with a compression molding machine, the molding material is shaped, and the molding pressure is maintained at 0.1 to 30 MPa to harden the molding material, and then the molded product is taken out to obtain a molded product. Specific molding conditions are preferably a mold temperature of 120 to 160°C in the mold and a molding pressure of 1 to 10 MPa for 1 to 2 minutes per mm of thickness of the molded product, and more preferably a mold temperature of 140 to 160°C and a molding pressure of 1 to 10 MPa for 30 to 90 seconds per mm of thickness of the molded product, because this improves productivity.
[0049] The molded products obtained from the fiber-reinforced molding material of the present invention have excellent appearance, bending strength, bending modulus, etc., and can therefore be suitably used for automobile parts, railway vehicle parts, aerospace aircraft parts, ship parts, housing equipment parts, sports parts, light vehicle parts, building and civil engineering parts, housings for office automation equipment, etc.
[0050] The present invention will now be described in more detail with reference to specific examples. EXAMPLES
[0051] (1) Preparation of Curable Resin Composition First, a resin solution (a) containing a brominated vinyl ester (A) was prepared as follows. In a 1 L flask equipped with a thermometer, nitrogen and air inlet tubes, a cooling condenser, and a stirrer, 365 parts by mass of epoxy resin (DIC Corporation's "Epiclon 152", tetrabromobisphenol A type epoxy resin (epoxy equivalent 365 g / equivalent, bromine content 48.1 mass%), 84 parts by mass of methacrylic acid, and 0.18 parts by mass of t-butylhydroquinone as a polymerization inhibitor were mixed and heated to 95°C under a gas flow of a 1:1 mixture of nitrogen and air. 0.9 parts by mass of triphenylphosphine was added as a catalyst to the flask, and the mixture was heated to 105°C and reacted for 12 hours, after which it was confirmed that the acid value was 1 or less. This indicated that brominated vinyl ester (A) had been synthesized. After that, the flask was cooled to about 90°C, and 20 parts by mass of 1,3-butanediol dimethacrylate was added as the unsaturated monomer (B), and the mixture was mixed and stirred without heating for 2 hours to obtain a resin solution (a) containing a brominated vinyl ester (A). The hydroxyl value of the obtained resin solution was 108 gKOH / g. The obtained resin solution contained 80 parts by mass of the brominated vinyl ester (A) and 20 parts by mass of 1,3-butanediol dimethacrylate when the total amount was 100 parts by mass.
[0052] Next, 100 parts by mass of the above-mentioned resin solution (a), 5.0 parts by mass of 1,3-butanediol dimethacrylate, 13.6 parts by mass of a mixture of polymethylene polyphenyl polyisocyanate and diphenylmethane diisocyanate ("Millionate MR-200" manufactured by Tosoh Corporation) as a polyisocyanate (C), 1.0 part by mass of "Trigonox 129-75" manufactured by Kayaku Nouryon Co., Ltd. (hydrocarbon solution containing 75% by mass of t-amylperoxyisopropyl carbonate) as a polymerization initiator (D), 1.0 part by mass of an internal release agent ("BYK P-9060" manufactured by BYK Japan KK), and 0.02 parts by mass of a polymerization inhibitor ("Polystop 7300P" manufactured by Hakuto Co., Ltd.) were mixed to obtain a thermosetting resin composition. The thermosetting resin composition contained 80 parts by mass of the brominated vinyl ester (A) and 25 parts by mass of the unsaturated monomer (B), and had a bromine concentration of 24.6% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.53.
[0053] (2) Preparation of SMC The thermosetting resin composition obtained above was applied to a polyethylene and polypropylene laminate film in an average coating amount of 1155 g / m using an SMC manufacturing device. 2After applying the curable resin composition to the laminate film, a carbon fiber (hereinafter, abbreviated as "reinforced fiber (E)") made by cutting a carbon fiber roving ("T700SC-12000-50C" manufactured by Toray Industries, Inc.) to a length of 12.5 mm was uniformly dropped from the air onto the curable resin composition so that the carbon fiber had no fiber directionality, was uniform in thickness, and had a carbon fiber content of 45 mass%, and was sandwiched between other laminate films to which the curable resin composition had been applied in the same manner, thereby impregnating the reinforcing fiber (E) with the thermosetting resin composition. The laminate film was then left to stand for 48 hours at a temperature of 40°C to obtain an SMC with a laminate film. The weight of the SMC was 2.1 kg / m 2 It was.
[0054] (3) Production of molded products The obtained SMC with laminate film was cut to 265 mm long x 265 mm wide, and two sheets of SMC with the laminate film peeled off were stacked together and placed in the center of a flat mold (mold interior area: 300 mm x 300 mm) heated to an upper mold temperature of 150°C and a lower mold temperature of 140°C. Compression molding was performed by heating and pressurizing at a surface pressure of 13 MPa for 3 minutes, resulting in a flat molded product measuring 300 mm long x 300 mm wide x 2 mm thick.
[0055] (4) Evaluation a) Viscosity When preparing the above-mentioned thermosetting resin composition, the resin composition in which the components other than the polyisocyanate (C) were mixed in advance, and the polyisocyanate (C) were each placed in an incubator set at a temperature of 25° C., and then the resin composition and the polyisocyanate (C) were mixed to prepare the thermosetting resin composition. The viscosity (25° C.) of the thermosetting resin composition immediately after mixing was measured with a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., “TVB-15”). b) Impregnation The obtained SMC with laminate film was cut in the thickness direction, and the cross section was observed at a magnification of 50 times using a digital microscope VHX-5000 (manufactured by Keyence Corporation), and the impregnation of the thermosetting resin composition into the reinforcing fiber (E) was evaluated according to the following criteria. Note that the cross sections were observed in two directions, one in any direction and the direction perpendicular to that direction (total of two directions with a length of 300 mm). <Evaluation> ⊚: There were two or less unimpregnated regions. ◯: There were 3 to 5 or less unimpregnated areas. △: There were 6 to 10 or less unimpregnated regions. ×: There were 11 or more unimpregnated regions or the unimpregnated regions were widespread.
[0056] c) Molding fluidity When the molded product was produced, the area where the SMC was not filled to the end of the flat mold (hereinafter abbreviated as "short shot") and the length of the burrs in the obtained molded product were visually observed, and the molding flowability was evaluated according to the following evaluation criteria. The width of the share edge of the flat mold was about 50 mm. <Evaluation> ⊚: No short shots occurred at all, and the short shots were within the range of the burr shear edges occurring in the molded product. 〇: Short shot area is 0cm 2 Super 3cm 2 or the molded product had flash that exceeded the share edge. △: Short shot area is 3cm 2 More than 5cm 2 or the molded product had flash that exceeded the share edge. ×: Short shot area is 5cm 2 or more, or burrs beyond the share edge were formed on the molded product.
[0057] d) Flame retardant The laminate film was peeled off from the obtained SMC with laminate film, and multiple SMC sheets were laminated so that the total thickness was 2 mm. The obtained laminate was placed in the center of a flat plate mold coated with a release agent, and compression molded in a compression molding machine under conditions of a pressure of 13 MPa, an upper mold temperature of 150°C, a lower mold temperature of 140°C, and a molding time of 3 minutes, and then cut into strips of 125 mm length x 13 mm width to prepare test pieces. A vertical combustion test was conducted using the obtained test specimen in accordance with UL94V. The top end of the test specimen was attached vertically to the clamp, and cotton was placed 300 mm below the test specimen. A blue flame (20 mm high) of methane gas was applied to the bottom end of the test specimen using a gas burner for 10 seconds, and the combustion time was measured. If the combustion lasted less than 30 seconds, the flame was applied for an additional 10 seconds, and the combustion time was measured. It was observed whether the cotton ignited due to the dropping of the drops, and whether combustion occurred at the clamp attachment position. These procedures were conducted on five test specimens. The UL94 evaluation criteria are shown in Table 1.
[0058] [Table 1] EXAMPLES
[0059] In this example, a thermosetting resin composition was obtained in the same manner as in Example 1, except that the amount of 1,3-butanediol dimethacrylate mixed with 100 parts by mass of the resin solution (a) was changed to 20.0 parts by mass. The thermosetting resin composition contained 40 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 21.9% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.53. Then, a laminated film-attached SMC and a molded article were obtained and evaluated in the same manner as in Example 1, except that the obtained thermosetting resin composition was used. EXAMPLES
[0060] In this example, a thermosetting resin composition was obtained in the same manner as in Example 1, except that the amount of 1,3-butanediol dimethacrylate mixed with 100 parts by mass of the resin solution (a) was changed to 10.0 parts by mass, and the amount of Millionate MR-200 added as the polyisocyanate (C) was changed to 17.9 parts by mass. The thermosetting resin composition contained 30 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 22.9% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.70. Then, a laminated film-attached SMC and a molded article were obtained and evaluated in the same manner as in Example 1, except that the obtained thermosetting resin composition was used. EXAMPLES
[0061] In this example, a thermosetting resin composition was obtained in the same manner as in Example 1, except that 20.0 parts by mass of methoxydiethylene glycol methacrylate was mixed with 100 parts by mass of the resin solution (a) instead of 5.0 parts by mass of 1,3-butanediol dimethacrylate. The thermosetting resin composition contained 40 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 21.9% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.53. Then, an SMC with a laminate film and a molded article were obtained and evaluated in the same manner as in Example 1, except that the obtained thermosetting resin composition was used. EXAMPLES
[0062] In this example, a thermosetting resin composition was obtained in the same manner as in Example 1, except that the amount of 1,3-butanediol dimethacrylate mixed with 100 parts by mass of the resin solution (a) was changed to 10.0 parts by mass, and 16.2 parts by mass of "Cosmonate LL" (aromatic polyisocyanate) manufactured by Mitsui Chemicals SKC Polyurethanes was used instead of 13.6 parts by mass of Millionate MR-200 as the polyisocyanate (C). The thermosetting resin composition contained 30 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 23.2% by mass. In addition, the molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.60. Then, an SMC with a laminate film and a molded article were obtained and evaluated in exactly the same manner as in Example 1, except that the obtained thermosetting resin composition was used.
[0063] [Comparative Example 1] In this comparative example, a thermosetting resin composition was obtained in the same manner as in Example 1, except that 1,3-butanediol dimethacrylate was not added at all to 100 parts by mass of the resin solution (a). The thermosetting resin composition contained 20 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 25.7% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.53. Then, an SMC with a laminate film and a molded article were obtained and evaluated in the same manner as in Example 1, except that the obtained thermosetting resin composition was used.
[0064] [Comparative Example 2] In this comparative example, a thermosetting resin composition was obtained in the same manner as in Example 1, except that the amount of 1,3-butanediol dimethacrylate mixed with 100 parts by mass of the resin solution (a) was changed to 35.0 parts by mass. The thermosetting resin composition contained 55 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 19.7% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.53. Then, an SMC with a laminate film and a molded article were obtained and evaluated in the same manner as in Example 1, except that the obtained thermosetting resin composition was used.
[0065] [Comparative Example 3] In this comparative example, a thermosetting resin composition was obtained in the same manner as in Example 1, except that the amount of 1,3-butanediol dimethacrylate mixed with 100 parts by mass of the resin solution (a) was changed to 10.0 parts by mass, and the amount of Millionate MR-200 added as the polyisocyanate (C) was changed to 19.2 parts by mass. The thermosetting resin composition contained 30 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 22.6% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.75. Then, a laminated film-attached SMC and a molded article were obtained and evaluated in the same manner as in Example 1, except that the obtained thermosetting resin composition was used.
[0066] [Comparative Example 4] In this comparative example, the resin solution (a') was prepared in the same manner as in Example 1, except that 20 parts by mass of phenoxyethyl methacrylate was used as the unsaturated monomer (B) instead of 20 parts by mass of 1,3-butanediol dimethacrylate when preparing the resin solution (a). Next, a thermosetting resin composition was obtained in the same manner as in Example 1, except that the resin solution (a') was used instead of the resin solution (a) and 20 parts by mass of methoxydiethylene glycol methacrylate was mixed as the unsaturated monomer (B) into 100 parts by mass of the resin solution (a'). The thermosetting resin composition contained 40 parts by mass of the unsaturated monomer (B) relative to 80 parts by mass of the brominated vinyl ester (A), and had a bromine concentration of 21.9% by mass. The molar ratio (NCO / OH ratio) of the isocyanate group (NCO) of the polyisocyanate (C) to the hydroxyl group (OH) of the brominated vinyl ester (A) was 0.53. An SMC with a laminate film and a molded article were obtained and evaluated in the same manner as in Example 1, except that the obtained thermosetting resin composition was used.
[0067] The evaluation results are shown in Table 2.
[0068] [Table 2]
[0069] As shown in Table 2, the thermosetting resin compositions of Examples 1 to 5 had good impregnation properties into the reinforcing fiber (E), with a rating of △ or higher, and the fiber-reinforced molding materials containing the resin compositions had molding fluidity of △ or higher, with the desired molding fluidity. Furthermore, the fiber-reinforced molding materials were able to produce molded products with flame retardancy of V1 or higher.
[0070] On the other hand, a molded article having excellent flame retardancy could be obtained by using the fiber-reinforced molding material using the thermosetting resin composition of Comparative Example 1. However, the impregnation of the reinforcing fiber (E) with the thermosetting resin composition was poor, and the fiber-reinforced molding material impregnated with the resin composition had a short shot area of 5 cm2 when a molded article was produced. 2The molding fluidity was rated as x. In addition, the fiber-reinforced molding materials using the thermosetting resin compositions of Comparative Examples 2 and 4 produced molded articles that did not meet the flame retardancy rating of V. The fiber-reinforced molding material using the thermosetting resin composition of Comparative Example 3 produced molded articles with a short shot area of 5 cm2 or less. 2 As a result, the molding fluidity was evaluated as x.
Claims
1. A brominated vinyl ester (A), an unsaturated monomer (B), a polyisocyanate (C), and a polymerization initiator (D), The unsaturated monomer (B) contains 1,3-butanediol dimethacrylate, The unsaturated monomer (B) is contained in an amount of 25 parts by mass or more and 40 parts by mass or less relative to 80 parts by mass of the brominated vinyl ester (A), A curable resin composition, wherein a molar ratio (NCO / OH ratio) of an isocyanate group (NCO) of the polyisocyanate (C) to a hydroxyl group (OH) of the brominated vinyl ester (A) is in the range of 0.40 or more and 0.70 or less.
2. The curable resin composition according to claim 1, comprising 20 parts by mass or more and 40 parts by mass or less of 1,3-butanediol dimethacrylate per 80 parts by mass of the brominated vinyl ester (A).
3. The curable resin composition according to claim 1 or 2, wherein the curable resin composition has a bromine concentration of 20 mass% or more.
4. 3. The curable resin composition according to claim 1, having a viscosity measured at 25°C in the range of 1,000 mPa·s to 12,000 mPa·s.
5. A fiber-reinforced molding material comprising the curable resin composition according to claim 1 or 2 and reinforcing fibers (E).
6. The fiber-reinforced molding material according to claim 5, containing the reinforcing fiber (E) in an amount of 20% by mass or more and 70% by mass or less.
7. A molded product using the fiber-reinforced molding material according to claim 6.
Citation Information
Patent Citations
Charger for raw material such as scrap for arc furnace
JP1987041583A